Seleksi dan Optimasi Karakter Fisik Bakteri Penghasil Fitase yang Diisolasi dari Sumber Air Panas di Guci, Tegal - Purwati, Catur Suci; Sajidan, Sajidan; Ratriyanto, Adi; Nuhriawangsa, Adi Magna Patriadi (Universitas Sebelas Maret (UNS), 2015)
The aimed of this study to isolate, select and characterize physically phytase-producing bacteriafrom hot springs in the Guci, Tegal. Isolation and enrichment of bacteria using Lurya Betani mediawith 2% of phytic acid substrate. Extraction of extracellular phytase thus obtained extract coarse andoptimization by loking at the relative activity at the difference in the resulting product. Phytaseproducingbacteria can be isolated from the hot springs of the Guci, Tegal with the highest relativeactivity in AG2 and AG2-1 colonies. The highest relative activity at a temperature of 55°C, pH 6, theincubation time of 90 minutes, the substrate concentration of 3% and a metal cofactor Ca2+ at aconcentration of 10-4M. Phytase-producing bacteria can be isolated from a hot spring in Guci, Tegaland have certain physical characteristics.